Феноменологическое обоснование влияния гидратации фосфогипсовой матрицы с редкоземельным наполнителем на ее радиационно-защитные свойства - Булат, Анатолий Федорович; Иванов, Валерий Анатолиевич; Голов, Константин Сергеевич; Ткаченко, Владимир Андреевич; Степаненков, Евгений Иванович (НТУ "ХПИ", 2015)
Обоснована адекватность предложенной феноменологической модели, в соответствии с которой гидратация фосфогипсовой матрицы приводит к аномально высокому, по сравнению с классическим законом Бугера, росту сечения взаимодействия рентгеновского излучения с радиационно-защитным (РЗ) наполнителем в виде редкоземельных элементов (РЗЭ). Установлена зависимость изменения уровня защиты персонала от рентгеновского излучения конструкциями из композиционного материала на основе фосфогипса от концентрации РЗЭ в нём и плотности материала.

The adequacy of the proposed phenomenological model, according to which phosphogypsum matrix hydration leads to the abnormally high in comparison with the classical Bouguer, growth-section of interaction of X-rays of radiation protection (RP) filler in the form of rare earth elements (REE). The dependence of changes in the level of personnel protection against X-ray structures of composite material based on phosphogypsum REE concentration and material density. This is achieved through the implementation of the mechanism of crystallization of hydrated cementations second, ensuring the destruction of agglomerated particles of REE, thereby increasing the number of ultra fine fraction, which in turn leads to an increase in cross-section of interaction of radiation with composite material construction. The regularities of changes in RP properties of structures made of composite material on the basis of phosphogypsum from the technological parameters of formation material. The technological parameters affecting the mechanism of interaction between hydrated binder with RP filler and providing weakening the intensity of X-ray and gamma radiation in the low and medium energy range of 1,4–1,5 times. The expediency of creation of RP structures made of composite material on the basis of phosphogypsum. The parameters of the RP structure and the efficiency of its use for protection against X-ray and gamma radiation.
Phenomenological justification influence hydration phosphogypsum matrix with rare earth filler on its radiation - protective properties
Keywords: гидратация; редкоземельные элементы; радиационная защита; ультрадисперсные частицы; phosphogypsum matrix; hydration; radiation protection; ultra particles